A corpus-based analysis of trainee translators' performance in medical translation. Issue 3 (2nd September 2021) - Pan, Yun
ABSTRACT: Medical translation plays an increasingly important role in mediating communication between medical professionals and facilitating medical research and practice. A close observation of empirical linguistic data of collective translated medical texts contributes to evaluating translators' professional performance in this specialized field. This article describes the application of corpus linguistics methods to analyse trainee translators' patterned use of the target language in medical translation. Based on an intensive review of corpus-based translation research, a case study is conducted among 27 Chinese trainee translators undertaking a Chinese-to-English medical report translation task. The translated texts in English are compiled to construct a target corpus. Standardized terminologies, patterns of semantic meaning, and the trainee translators' discursive preferences are investigated and characterized. The analyses show that linguistic evidence retrieved from learner corpora is of vital importance to evaluate trainee translators' lexical choices and discursive preferences in their translation practice, thus contributes to enhancing their critical language awareness of the cultural dimension in medical translation. The research findings have implications in program development for specialized translator training, particularly how to integrate selective corpus data into the design of inductive, reflective translation tasks.